2007
DOI: 10.1200/jco.2007.25.18_suppl.2564
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, metabolism, and excretion of 14C gimatecan (LBQ707) after oral administration in patients with advanced cancer

Abstract: 2564 Background: Gimatecan (Gim), a new potent oral topoisomerase I inhibitor is a lipophilic 7-oxyiminomethyl derivative of camptothecin. Its in vitro cytoxicity is more sustained than CPT-11 and topotecan, it has excellent anti-tumor activity in mouse xenografts, and shown good tolerability with Ph I activity. The study aim was to profile its disposition in cancer patients. Methods: 4 patients with advanced cancer received a single oral 1.5 mg dose of [14C] Gim (60 μCi) followed by standard Gim treatment on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Gimatecan have not only shown better tumor penetration but these have also shown to better initiate the cytotoxic response owing to their rapid intracellular accumulation, and entrapment of DNA–topoisomerase I complex in its normal transient conformation . Altogether, these studies have shown gimatecan as promising molecule against multiple metastatic cancers …”
Section: Drugs Targeting Different Type I Topoisomerasesmentioning
confidence: 98%
“…Gimatecan have not only shown better tumor penetration but these have also shown to better initiate the cytotoxic response owing to their rapid intracellular accumulation, and entrapment of DNA–topoisomerase I complex in its normal transient conformation . Altogether, these studies have shown gimatecan as promising molecule against multiple metastatic cancers …”
Section: Drugs Targeting Different Type I Topoisomerasesmentioning
confidence: 98%